2017
DOI: 10.1177/0309364616664151
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of core stabilization exercise in adolescent idiopathic scoliosis

Abstract: Core stabilization training in addition to traditional exercises was more effective than traditional exercises alone in the correction of vertebral rotation and reduction of pain in adolescent idiopathic scoliosis. Clinical relevance Stabilization exercises are more effective in reducing rotation deformity and pain than traditional exercises in the conservative rehabilitation of adolescent idiopathic scoliosis. These improvements suggest that stabilization training should be added to rehabilitation programs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 36 publications
2
58
0
8
Order By: Relevance
“…Exercise was applied 3 times a week for 12 weeks was found to be effective even at a 40-degree or higher Cobb’s angle 32 ) . Core stabilization training in addition to traditional exercises was effective in the correction of vertebral rotation and reduction of pain in AIS 33 ) . A 10-week core strengthening exercises decreases Cobb angle and improves back muscle strength in patients with functional scoliosis 34 ) .…”
Section: Discussionmentioning
confidence: 98%
“…Exercise was applied 3 times a week for 12 weeks was found to be effective even at a 40-degree or higher Cobb’s angle 32 ) . Core stabilization training in addition to traditional exercises was effective in the correction of vertebral rotation and reduction of pain in AIS 33 ) . A 10-week core strengthening exercises decreases Cobb angle and improves back muscle strength in patients with functional scoliosis 34 ) .…”
Section: Discussionmentioning
confidence: 98%
“…it was proved superior to traditional exercises in conservative rehabilitation of AiS patients. Therefore, it is particularly recommended to add stabilization exercises to the current protocol of exercises for patients with AiS [26].…”
Section: Discussionmentioning
confidence: 99%
“…One previous study found that core stabilization was effective in the correction of vertebral rotation and reduction of pain in AIS patients. 11 However, a 2013 systematic review found insufficient high-quality evidence that corrective exercises decreased curve magnitude in patients with AIS. 12 The results of our study present no significance between completing a side plank or front plank for 6 months on Cobb angle.…”
Section: Discussionmentioning
confidence: 99%